50‐4: Standardizing Fundamental Criteria for Near Eye Display Optical Measurements: Determining the Eye‐box. Issue 1 (25th September 2020) - Varshneya, Rupal; Draper, Russell S.; Penczek, John; Pixton, Bruce M.; Nicholas, Terence F; Boynton, Paul A.
Abstract : The eye‐box is one of the fundamental characteristics of a near‐eye display. A complete 3D evaluation of the eye‐box is generally difficult and time consuming. A new efficient eye‐box measurement is demonstrated and compared with current methods.